THE INFLUENCE OF ADVERTISING ATTRACTIVENESS, PRODUCT QUALITY, BRAND IMAGE ON PURCHASING DECISIONS AND CUSTOMER LOYALTY IN PEKANBARU COMMUNITY PURCHASING LE MINERALE WATER - , (LUCRUM : Jurnal Bisnis Terapan; Vol 5 No 3 (2025): LUCRUM : Jurnal Bisnis Terapan, 2026)
The purpose of this research is to determine the influence of advertising attractiveness, product quality, brand image on purchasing decisions and customer loyalty when purchasing Le Minerale water for the Pekanbaru community. The population in this research is consumers of Le Minerale Water in Pekanbaru City, the exact number of which is not known. So this research took the number of respondents to be 150 respondents for research. The sampling technique used was purposive sampling. Data analysis used multiple linear regression analysis. The results of this research explain that advertising attractiveness has a positive and significant influence on purchasing decisions, product quality has a positive and significant influence on purchasing decisions, advertising attractiveness has a positive and insignificant influence on customer loyalty, product quality has a positive and insignificant influence on customer loyalty, brand image has a positive and significant influence on Customer Loyalty, Purchasing Decisions have a positive and significant influence on Customer Loyalty.